La Montarana: a Late Bronze Age settlement by Tarquinia (Viterbo, Italy). With Appendix on faunal remains - Carlo Persiani; Francesca Alhaique (IpoTESI di Preistoria)
A series of surveys carried out between 1970 and 1987 by volunteers of the Gruppo Archeologico Romano collected a significant quantity of pottery sherds on the Montarana hill, located on the hilly slopes opposite to the city of Tarquinia. This contribution presents around 200 significant fragments from the more than the 1000 of those collected, with their typological and chronological classification. Most of them belong to the Subapennine Late Bronze Age and the Protovillanovan Final Bronze Age. Some sherds also appear which can be better dated to older phases of the Bronze Age. The lack of fragments referable to the final phase of the Final Bronze Age suggests that the settlement of Montarana early contributed to the emergence of the nearby site of Civita di Tarquinia as the dominant center of the territory even before the beginning of the Iron Age.